Ionogels: Preparation, Properties and Applications - Yan, Chang‐Cun; Li, Weizheng; Liu, Ziyang; Zheng, Sijie; Hu, Yin; Zhou, Yingjie; Guo, Jiangna; Ou, Xu; Li, Qingning; Yu, Jiangtao; Li, Legeng; Yang, Mingchen; et al. (Advanced functional materials, 2024)
Ionogels, composed of ionic liquids and supporting networks, possess a plethora of exceptional properties, including nonvolatility, remarkable thermal and electrochemical stability, elevated mechanical strength, as well as outstanding ionic conductivity. Based on these extraordinary characteristics, ionogels have found extensive applications in diverse fields encompassing functional materials, sensors, soft electronics, solid electrolytes, and biomedicine. In recent years, ionogels have witnessed significant advancements and emerged as a highly popular subject matter. Consequently, this review provides a comprehensive overview of the latest progress made in the realm of ionogels. The preparation methods of ionogels are initially introduced following a concise introduction. Subsequently, the properties of ionogels, encompassing mechanical properties, high and low temperature resistance, ionic conductivity, stimuli‐response properties, self‐healing properties, recyclability and their structure‐property relationships, are comprehensively discussed. Moreover, recent advancements in the utilization of ionogels in solid electrolytes, ionic skins, soft electronics, adhesions and other domains are also elaborated upon extensively. Finally, after a succinct summary, challenges and prospects regarding the future development of ionogels are thoroughly deliberated.